Spatial narratives: redefining permanent gendered spaces for temporal female traders in Eveline Street, Katutura, Windhoek - Shaimemanya, Tuwilika Nailoke (School of Architecture, Planning and Geomatics, 2022)
In Windhoek and other South African cities six of eight traders are women. As noted by Huda Tayob, spaces occupied by female traders are sites of refuge and care within a highly contested urban realm. In Eveline Street, Katutura, Windhoek the capitalist uneven spatial development has led to continued movement from rural areas to the city. Yet the plethora of opportunities the street offers are limited when it comes to gender mainstreaming. The approach for designing has largely been self-built and conditioned for more men against women trading in the street. Furthermore, research shows that women are more likely to use their earnings on necessities such as food, clothing and education. It also shows that women constantly have to battle for safety in public spaces. The design component of this research study seeks firstly, to facilitate women's access to gendered spaces in these locales by taking on a feminist approach to urban design, by building on the thriving nature of everyday spaces on the street. Secondly, to establish how a collaborative design process between female traders and urban designers may result in better access to infrastructure, recreational spaces and public care within existing public spaces, across multiple scales in Eveline Street. Thirdly, to achieve the trade potential for women in order to ensure food security, vital job creation and poverty reduction. The methodologies used to represent the spatial processes in Eveline Street included: Participatory design methodologies, focus groups, storytelling, non-participant observations, video analysis, data analysis and desk research.